2019
DOI: 10.1016/j.neuropsychologia.2019.107218
|View full text |Cite
|
Sign up to set email alerts
|

Learning own- and other-race facial identities: Testing implicit recognition with event-related brain potentials

Abstract: Exposure to varying images of the same person can encourage the formation of a representation that is sufficiently robust to allow recognition of previously unseen images of this person. While behavioural work suggests that face identity learning is harder for otherrace faces, the present experiment investigated the neural correlates underlying own-and other-race face learning. Participants sorted own-and other-race identities into separate identity clusters and were further familiarised with these identities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 80 publications
(135 reference statements)
0
10
0
Order By: Relevance
“…It was suggested to reflect the processing of metric distances between the facial features (Halit et al, 2000;Kaufmann & Schweinberger, 2012;Latinus & Taylor, 2006;Mercure et al, 2008). A modulation of the P200 by face race has been found by some studies (but see: Hahn et al, 2012;Herzmann et al, 2011;Tüttenberg & Wiese, 2019;Vizioli, Foreman, et al, 2010;Yong et al, 2020), consistently showing larger amplitudes to OWN-as opposed to other-race faces (Chen et al, 2013;Lucas et al, 2011;Stahl et al, 2008Stahl et al, , 2010Tanaka & Pierce, 2009;Wang et al, 2020;Wiese, 2012Wiese, , 2013Wiese et al, 2014;Wiese & Schweinberger, 2018; but see Anzures & Mildort, 2021;) (see Tables 3-5). As for the latency, no race effect was generally found (Anzures & Mildort, 2021;Hahn et al, 2012;Wang et al, 2020; but see Chen et al, 2013).…”
Section: P200 (Or Occipito-temporal P2)mentioning
confidence: 89%
See 3 more Smart Citations
“…It was suggested to reflect the processing of metric distances between the facial features (Halit et al, 2000;Kaufmann & Schweinberger, 2012;Latinus & Taylor, 2006;Mercure et al, 2008). A modulation of the P200 by face race has been found by some studies (but see: Hahn et al, 2012;Herzmann et al, 2011;Tüttenberg & Wiese, 2019;Vizioli, Foreman, et al, 2010;Yong et al, 2020), consistently showing larger amplitudes to OWN-as opposed to other-race faces (Chen et al, 2013;Lucas et al, 2011;Stahl et al, 2008Stahl et al, , 2010Tanaka & Pierce, 2009;Wang et al, 2020;Wiese, 2012Wiese, , 2013Wiese et al, 2014;Wiese & Schweinberger, 2018; but see Anzures & Mildort, 2021;) (see Tables 3-5). As for the latency, no race effect was generally found (Anzures & Mildort, 2021;Hahn et al, 2012;Wang et al, 2020; but see Chen et al, 2013).…”
Section: P200 (Or Occipito-temporal P2)mentioning
confidence: 89%
“…A modulation of the N250 amplitude by face race has been supported by large evidence (Balas & Nelson, 2010;Brebner et al, 2011;Herrmann et al, 2007;Herzmann, 2016;Herzmann et al, 2011Herzmann et al, , 2018Liu et al, 2014;Sun et al, 2014;Tanaka & Pierce, 2009;Tüttenberg & Wiese, 2019;Wiese et al, 2014;Wiese & Schweinberger, 2018), while a minority of the studies found no N250 face race effect (Lv et al, 2015;Vizioli, Foreman, et al, 2010;Wiese, 2012;Zhou et al, 2015) (see Tables 3-5). The majority of the studies found larger N250s to OTHER-as opposed to own-race faces (Balas & Nelson, 2010;Brebner et al, 2011;Herzmann, 2016;Herzmann et al, 2011Herzmann et al, , 2018Liu et al, 2014;Sun et al, 2014;Wiese et al, 2014;Wiese & Schweinberger, 2018), while a minority found larger N250s to OWN-as opposed to otherrace faces (Balas & Nelson, 2010;Herrmann et al, 2007;Tanaka & Pierce, 2009;Tüttenberg & Wiese, 2019). Larger amplitudes to other-race faces were ascribed to increased individuation difficulties or processing effort for otherrelative to own-race faces (Schweinberger, 2011); larger amplitudes to own-race faces were ascribed to familiarity processes, in line with an effect of individual-level training with objects on the N250 (e.g., cars, birds; Scott et al, 2008;Scott, Tanaka, et al, 2006) and with the role of the N250 in face familiarity …”
Section: N250mentioning
confidence: 95%
See 2 more Smart Citations
“…These neural evaluations help in computing the age, gender and demographic information of a human that has a momentous effect on the perceived as well as perceiver (Yao and Zhao, 2019; Short et al , 2012; Thornton et al , 2019). Among these most notorious personal traits, the race is said to be the most dominant, and it is empirically portrayed with the omni relevance corresponding to the perceptual tasks and the communal cognitive (Proietti et al , 2019; Vo et al , 2018; Tüttenberg and Wiese, 2019). In general, the Wiki encyclopedia defines race as “Race is a classification system, used to categorize humans into large and distinct populations or groups by heritable, phenotypic characteristics, geographic ancestry, physical appearance, ethnicity and social status” (Wu et al , 2018; Karamizadeh and Abdullah, 2018).…”
Section: Introductionmentioning
confidence: 99%